Business Intelligence Healthcare Model: Getting the Right Requirements for Malaysian Rural Citizens - Azizah Ahmad; Sajaratul Huda Shafie; Azman Ta’a; Rafidah Abdul Razak (International Journal of Supply Chain Management, 2016)
It is a big challenge for Malaysian healthcare authorities in providing services to rural communities. To meet up with the challenges, a concept called business intelligence (BI) is employed for their informed decision-making that utilizes their enormous data. However, only a few of BI initiatives have their success stories as many are still struggling to justify the investments. Among the most reason of the failures were that BI requirements were overlooked, leading to poor BI deployments. Taking rural healthcare in Malaysia as a case study, the paper attempts to model BI requirements using goal-oriented approach. Rural healthcare BI requirements were modelled two-folds: (1) decision making requirements, cantered on stakeholders; and (2) BI data requirements, focused on organizational and decisional aspects. The model can guide BI developers on the process and data needed in rural healthcare strategic decision-making. Theoretically it provides new insights and facilitates the improvement of new healthcare knowledge.